Klinička biohemijska procena elemenata u tragovima i insulinu sličnog faktora rasta-I kod dece sa kratkim rastom: dijagnostički i korelacijski uvidi iz kohorte Guangdžou: Trace Element–IGF-I Biomarkers in Short Stature - Huang, Bei; Wang, Xiaojun; Zhang, Ying (Journal of Medical Biochemistry, 2025)
Background: Trace elements and insulin-like growth factor-I (IGF-I) are critical biochemical regulators of skeletal growth and endocrine function. However, limited data are available regarding their laboratory correlations in pediatric short stature. This study aimed to evaluate the biochemical profiles of calcium, magnesium, zinc, and lead, together with serum IGF-I levels, and to assess their diagnostic significance in children with growth retardation in the Guangzhou region.Methods: A total of 876 children aged 2–12 years were enrolled, including 276 with growth retardation, 300 with short stature, and 300 healthy controls. Serum trace elements and IGF-I concentrations were determined using standardized clinical chemistry assays in a hospital laboratory. Intergroup differences were analyzed using ANOVA, and multivariate logistic regression was employed to identify independent biochemical predictors of growth retardation.Results: Children with growth retardation exhibited significantly lower serum levels of calcium, magnesium, and zinc, and elevated blood lead concentrations compared with controls (P